Electrical characteristics of bendable a-ITGZO TFTs on colorless polyimide substrates. (19th May 2020) - Lee, Hosang; Cho, Kyoungah; Kim, Donghyun; Kim, Sangsig
Abstract: In this study, we fabricate amorphous indium tin gallium zinc oxide (a-ITGZO) thin-film transistors (TFTs) on colorless polyimide (CPI) substrates and examine their electrical characteristics as functions of the bending radius. A representative a-ITGZO TFT shows typical n -type behavior and operates with a mobility of 34.32 cm 2 V −1 s −1, threshold voltage of −0.71 V, subthreshold swing of 169 mV, and on/off ratio of 2 × 10 7 . The a-ITGZO TFT operates stably even under a bending radius of 2 mm, regardless of the upward or downward bending. The thickness of the thin CPI substrate contributes to the stable operation of the bent TFT.